MODEL TRANSPORTASI MENGHITUNG BIAYA TERENDAH MENGGUNAKAN METODE MODIFIED DISTRIBUTION (MODI) - Wahyu Sofyanti Dewi; Elizabeth Nurmiyati Tamatjita; Yuliani Indrianingsih (Compiler, 2016)
Modified Distribution (MODI) method of the operation research’s in Sekolah Tinggi Teknologi Adisutjipto Informatic Engineering is one of method which optimal solution low cost in the transportation model. MODI is using Northwest Corner method to determine the initial allocation, which will be processed to obtain a more optimal solution. MODI method is aplied to a desktop-based application that aims to help lecturer on presentation material. The results of 2 test on 1 primary user respondent 85,81% for 30 questions, test of 30 secondary user respondent with, Display/Graphical User Interface (GUI) (74,67%), Speed/Conveniences Of Access to information (80,92%), Accuracy Of Information (82,89%), and User Satisfaction (81,90%). Low cost application of Transportation Model with MODI method is very good.